(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To find out the correlation of the lower urinary tract symptoms with age, fluid intake, economical status, education and area of residence. Subjects and Methods: One thousand males, above 50 years of age, attending their patients at Services Hospital Lahore, were interviewed with a questionnaire. The questionnaire comprises of International prostate symptom score (IPSS) questionnaire, bothersome score chart, quality of life chart and various questions about their age, drinking habits, economical status, education and area of residence. The persons who were known case of Diabetes mellitus, Congestive cardiac failure, Neurogenic bladder, vesical stone or stone in lower ureter, urinary tract infection, urinary bladder growth or patients who were taking medicine which effect urinary system were excluded from the study. Results: Lower urinary tract symptoms were common and increased with increase in age. Both bothersome and quality of life were effected with the severity of symptoms. The persons taking fluid before going to bed suffered more with lower urinary tract symptoms although there was no significant difference between the persons taking more or less fluid in 24 hours. There was no significant differences between the prevalence of low income group and high income group, literate and illiterate group and groups according to area of residence. Conclusion: The high incidence of lower urinary tract symptoms may indicate high prevalence of benign prostatic enlargement, but other causes are also involved. As lower urinary tract symptoms adversely affect quality of life, improved treatment options and increased public awareness of factors affecting lower urinary tract symptoms are needed.